2022
DOI: 10.1039/d2gc02622h
|View full text |Cite
|
Sign up to set email alerts
|

Turning waste into wealth: efficient and rapid capture of gold from electronic waste with a thiourea functionalised magnetic core stirring rod adsorbent and its application for heterogeneous catalysis

Abstract: Selective capture and separation of gold from secondary resources is an urgently demand to offset the increasing depletion of gold resources, to meet the sustainable supply of precious metal resources...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…In addition, X-ray photoelectron spectroscopy (XPS) analysis was further conducted to investigate the gold adsorption mechanism of MMNR-IIP-YS. As shown in Figure b, the XPS spectra of MMNR-IIP-YS before and after the uptake of gold were recorded to disclose the strong bonding site, a new peak appeared near 86.05 eV and was related to the Au 4f peaks, supporting that the gold ion was successfully captured by MMNR-IIP-YS. It can be seen from the high-resolution spectra of Au 4f (Figure c) that the peaks at 87.62 and 83.91 eV correspond to the Au 4f 5/2 and Au 4f 7/2 of Au­(III), indicating that the adsorption process occurred only by chelation without redox reaction, which was the reason why the adsorption amount of MMNR-IIP-YS was not high .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, X-ray photoelectron spectroscopy (XPS) analysis was further conducted to investigate the gold adsorption mechanism of MMNR-IIP-YS. As shown in Figure b, the XPS spectra of MMNR-IIP-YS before and after the uptake of gold were recorded to disclose the strong bonding site, a new peak appeared near 86.05 eV and was related to the Au 4f peaks, supporting that the gold ion was successfully captured by MMNR-IIP-YS. It can be seen from the high-resolution spectra of Au 4f (Figure c) that the peaks at 87.62 and 83.91 eV correspond to the Au 4f 5/2 and Au 4f 7/2 of Au­(III), indicating that the adsorption process occurred only by chelation without redox reaction, which was the reason why the adsorption amount of MMNR-IIP-YS was not high .…”
Section: Resultsmentioning
confidence: 85%
“…The structure–property relationship of adsorbents can provide useful guidance for designing and developing potential adsorbents. , The exploration of high-performance adsorbents is the key to improving the coefficient of performance by adjusting the number and accuracy of identification sites and the pore structure of adsorbents. , On the one hand, ion imprinting technology is used to prepare ion-imprinted polymers (IIPs) with precise size, shape, and function of recognition sites based on enzyme–substrate and antigen–antibody interactions developed in nature to enable specific recognition of target ions in complex environments. , Due to the advantages of simple preparation, fixed hole size, fast adsorption rates, high selectivity, strong regeneration ability, and good environmental stability, they are widely used in solid-phase extraction, membrane separation, and sensors for metal ions . On the other hand, the yolk–shell nanostructures confer good performance as ideal carriers and nanoreactors due to their large void space and specific surface area. In particular, the presence of cavities not only allows maximum exposure of the active site for effective utilization but also accelerates molecular or ion transfer, and the shell acts as a protection against agglomeration and loss of core material. , In addition, magnetic nanorods are regarded as one of the most promising adsorbent carriers because of their synergetic characteristics of self-stirring and magnetic separation, which not only reduce the solubility loss of the adsorbent but also significantly promote the mass transfer and efficiency of the adsorption process. As a consequence, based on these advantages, the construction of IIPs with a yolk–shell nanostructure on the surface of magnetic nanorods will significantly improve the performance of the adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic reduction of nitroaromatics to the corresponding aromatic amines is one of the most important reactions, as aromatic amines are essential organic intermediates for a variety of high-value chemicals such as perfumes, plastics, pharmaceuticals, and pesticides. Recently, it has been reported that the reduction of nitroaromatics can be facilitated at room temperature in the presence of NaBH 4 . , Nowadays, catalysts based on noble metals (Ru, Pd, Ag, Pt, Au, etc.) are widely utilized for the reduction of nitroaromatics due to their high catalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…However, its reduction product 4-aminophenol (4-AP) is an important chemical and pharmaceutical intermediate . Currently, the reduction reaction from 4-NP to 4-AP is mostly catalyzed by novel metals. The usage of novel metals has hindered the industrial application of the reduction product 4-AP. Furthermore, the novel metal particles (or the active sites) on the substrate surface easily fall off, resulting in poor stability and reusability.…”
mentioning
confidence: 99%
“…It is known that the reduction of 4-NP generally takes place on the surface of the catalysts. There is an “induction time” of less than 5 s before the reduction of 4-NP as it needs time to absorb 4-NP onto the surface of the CuNi-MOFs and dissolve oxygen to react with NaBH 4 (Figure f) . The whole reaction is about 15 s (Figure f).…”
mentioning
confidence: 99%